Analisis Laporan Arus Kas Pada Pemerintah Kabupaten Demak Tahun Anggaran 2008-2009 - (Jurusan Akuntansi, Politeknik Negeri Semarang), Ema Giyan Subekti, Mohamad Hasanudin (Teknis, 2014)
The purpose of analyzing this is to analyze Cash Flow Statement at Pemerintah Kabupaten Demak for fiscal year 2008-2009 with using the growth of cash flow analysis and free cash flow analysis. The collection of data derived from Dinas Pengelolaan Keuangan dan Kekayaan Daerah in Pemerintah Kabupaten Demak that is by interview and literature study. Writing method used is the method of data description and exposition. Description Of the method used to find a general overview of Pemerintah Kabupaten Demak and Dinas Pengelolaan Keuangan dan Kekayaan Daerah, while the method of Exposition in the writing of data is to analyze the cash flow statement of the fiscal Year 2008-2009 in Pemerintah Kabupaten Demak. The results show that the growth of cash flow for each of the exiting cash flow activity in Cash Flow Statement at Pemerintah Kabupaten Demak is have good performance of cash financial, where as calculation of free cash flow is produce that have increase in financial performance on year 2009 than in year 2008.Keywords: Cash Flow Statement, Cash Flow Growth Analysis, and Free Cash Flow Analysis.